(untitled) (Research, Society and Development, 2021)
In communication services, the quality and integrity of the voice signal at the receiver is a relevant factor that telephone operators must consider. In this article, we study the impact of degradation that occurs in the transmission channel on the transmitted voice signal. Therefore, key parameters are used, such as the average opinion score (MOS) related to the voice signal and the bit error rate (BER), in order to qualitatively and quantitatively evaluate the speech signal in each scenario. A modulation simulation scenario is used, which considers the AWGN, Rician and Rayleigh fading channels, and two modulations: BPSK and QAM. These channels have different configuration parameters. Experimental results show that there are certain MOS quality index values ​​for each type of channel with a specific configuration, showing that for each transmission scenario there is a need for adaptations in the modulation-channel-gain combination to obtain better performance.